eShadow+: Mixed Reality Storytelling Inspired by Traditional Shadow Theatre - Moumoutzis, Nektarios; Christoulakis, Marios; Xanthaki, Chara; Pappas, Nikos; Maragkoudakis, Yiannis; Christodoulakis, Stavros; Paneva-Marinova, Desislava (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
eShadow is a digital storytelling platform inspired by traditionalShadow Theatre. It enables the creation of digital stories within a project-based approach that may start from scenario development and include the creation of digital puppets and sceneries, the set-up and recording of story scenes and the final assembly of a digital story. This paper presents details about eShadow architecture, features and how its use has been enhanced, employing the PerFECt framework, to combine it with immersive technologies such as projection mapping, to create mixed reality installations that offer rich learning experiences to participants in informal learning settings. Two installations are described and compared. The evaluation results demonstrate the effectiveness of the approach towards engaging learning experiences that combine mixed reality approaches with arts such as black light theatre.
Keywords: Onlife Communities; Digital Storytelling; Shadow Theater